An integral sliding mode fault tolerant control for a class of non‐linear Lipschitz systems. Issue 3 (21st December 2020) - Ashraf, Muhammad Ammar; Ijaz, Salman; Zou, Yao; Hamayun, Mirza Tariq
Abstract: This paper proposes an active fault‐tolerant control (FTC) strategy for a class of non‐linear Lipschitz systems. The proposed FTC approach employs the integral sliding mode control (ISMC) technique due to its inherent capability of dealing with system uncertainties. First, under the nominal fault‐free condition, the linear matrix inequality technique is introduced to design the primary controller for the non‐linear Lipschitz system. To accommodate the actuator faults/failures, the ISMC law is combined with a control allocation scheme that distributes the control signals to the redundant actuators. A non‐linear octorotor system is then used as a test bench to validate the tolerance performance of the proposed FTC strategy. In particular, the proposed FTC strategy is applied for the inner‐loop control, while in the outer loop, a fractional‐order control approach is used to achieve the precise longitude and latitude control. Finally, various simulations are performed to justify the effectiveness of the proposed control scheme.